Production Risk Management of Organic Rice in Special Region of Yogyakarta - Efi Nikmatu Sholihah; Irham Irham; Masyhuri Masyhuri (HABITAT, 2018)
Risk management is an important thing in organic farming to obtain optimal yields. The objective of the study are: (1) To know the factors affecting the production of organic rice in Special Region of Yogyakarta, (2) Estimate the level of production risk and the factors that affect the risks production of organic rice in Special Region of Yogyakarta, and (3) Determine the risk management of organic rice production. Data were collected from 30 respondents with proportional random sampling method. The factors affecting production and production risk of organic rice were analyzed using multiple linear regression with ordinary least square model, while the level of risk was analyzed by using coefficient of variation. The results showed by adding variables of land area and organic fertilizers can increase the production of organic rice in Special Region of Yogyakarta. Liquid fertilizer has significant effect to reduce risk of organic rice production. While the variables of land area and organic fertilizers have the potential to increase production risks. Based on the results of risk analysis it is known that the risk of organic rice production is relatively low because the value of coefficient of variation is low as well.